Fund Assistance From Amal and Zakat Agencies: Will It Help Effectiveness and Improve MSME Performance in The Time of The Covid-19 Pandemic? (Case Study of Lazismu Indonesia's MSME Empowerment Program) - Nadia Fathurrahmi Lawita; Wan Laura Hardilawati (Jurnal Ilmiah Ekonomi Islam, 2021)
MSMEs are currently a topic of discussion that needs attention, considering how the condition of MSMEs can have a significant impact on the national economy, however, the Covid-19 Pandemic has strongly impacted economic decline accompanied by the closure of many MSMEs. To revive the existence of MSMEs, currently a lot of assistance is provided in the form of funds and guidance for MSME players, one of which is from the Lazismu Institute. This study aims to analyze the effectiveness of Lazismu funding on the performance of MSMEs using mix methods, where the result is that the assistance from Lazismu affects the performance of MSMEs. The results showed that the UMKM assistance provided by Lazismu was considered useful and effective in supporting the performance of MSMEs, besides that the existence of business assistance and training could also support the improvement of MSME performance